2013
DOI: 10.1364/oe.21.021293
|View full text |Cite
|
Sign up to set email alerts
|

Integration of microfluidics with grating coupled silicon photonic sensors by one-step combined photopatterning and molding of OSTE

Abstract: We present a novel integration method for packaging silicon photonic sensors with polymer microfluidics, designed to be suitable for wafer-level production methods. The method addresses the previously unmet manufacturing challenges of matching the microfluidic footprint area to that of the photonics, and of robust bonding of microfluidic layers to biofunctionalized surfaces. We demonstrate the fabrication, in a single step, of a microfluidic layer in the recently introduced OSTE polymer, and the subsequent una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In the meantime, these designs usually bring increased coupling loss. When it comes to edge couplers, despite the apparent advantages such as high coupling efficiency, broad bandwidth, and low dependence on polarization, the main limits lie in that edge coupling only allows the alignment of fiber with the coupler at the chip facet, which is less convenient compared with grating couplers that support wafer-level testing at different positions on the wafer plane [116][117][118]. Meanwhile, edge couplers generally have larger footprints in the longitudinal dimension.…”
Section: A Brief Comparison Between Edge Couplers and Vertical Couplersmentioning
confidence: 99%
“…In the meantime, these designs usually bring increased coupling loss. When it comes to edge couplers, despite the apparent advantages such as high coupling efficiency, broad bandwidth, and low dependence on polarization, the main limits lie in that edge coupling only allows the alignment of fiber with the coupler at the chip facet, which is less convenient compared with grating couplers that support wafer-level testing at different positions on the wafer plane [116][117][118]. Meanwhile, edge couplers generally have larger footprints in the longitudinal dimension.…”
Section: A Brief Comparison Between Edge Couplers and Vertical Couplersmentioning
confidence: 99%
“…This leads to large footprint area and low sensitivity. For example, recent results on using single microring resonators for glucose and ethanol detection showed that sensitivity of 108nm/RIU [2,15], 200nm/RIU [16] or using microfluidics with grating for ethanol sensor with a sensitivity of 50nm/RIU [17]. Silicon waveguide based sensors has attracted much attention for realizing ultra-compact and cheap optical sensors.…”
Section: Introduction mentioning
confidence: 99%
“…For example, recent results showed that the sensitivities of 108 nm/RIU [2,12] and 200 nm/RIU [13] for glucose and ethanol detection using single microring resonator can be achieved. In addition, by using microfluidics with grating, ethanol sensor with a sensitivity of 50 nm/RIU can be obtained [14]. The silicon waveguide based sensors have attracted much attention for realizing ultra-compact and cheap optical sensors.…”
Section: Introductionmentioning
confidence: 99%